(untitled) (Jurnal Pustaka, 2026)
This research is entitled Identification of Kigo and Kireji and Interpretation of Messages in Haiku Book For Children. This research aims to determine the types of kigo and kireji as well as the interpretation of messages in haiku books for children. In this research, the method used is a descriptive method with a qualitative approach. The theories used in this research are semiotic theory by Pierce and semantic theory by Keraf. Based on the research results, it shows that the types of kigo consist of Doubutsu (animals) and Shokubutsu (plants). Then the types of kireji consist of suzumenoko, ya, nari and ume. The interpretation of the message in the haiku book for children describes the meaning of life, to appreciate the beauty and magic that occurs in our daily lives. Apart from that, this haiku teaches how to find happiness, strength in living life and self-protection as well as the importance of appreciating and celebrating the small things in life. So the closeness of Japanese people to nature is shown by haiku-haiku which means natural phenomena, culture and celebratory activities.